Joined-up governance at local level - Araújo, Joaquim Filipe (2019)
This article analyzes an interorganizational cooperation initiative among local actors to improve local policy coordination. Based on the network approach to local governance, the study provides insight into why local actors cooperate and how cooperation works. The analysis is based on interviews with local authorities, public managers and local politicians.